Novel carbamoyl type quinine and quinidine based chiral anion exchangers implementing alkyne-azide cycloaddition immobilization chemistry - Hettegger, Hubert; Kohout, Michal; Mimini, Vebi; Lindner, Wolfgang (Journal of chromatography. A, 2014)
The synthesis and chromatographic evaluation of a series of new Cinchona derived chiral weak anion exchangers is presented. Huisgen Cu(I) mediated alkyne-azide cycloaddition, so-called click chemistry, was used as an immobilization strategy. In this way it was possible to immobilize about 90% of offered selector via 1,2,3-triazole linker, which displays a more efficient way of binding the selector to modified silica compared to common radical mediated thiol-ene addition. Problems associated with potential radical scavenging properties of chiral selectors thereby could be circumvented. The evaluation of the synthesized chiral stationary phases regarding chromatographic behavior was carried out using polar organic mode mobile phase composition and a set of representative chiral organic acids. Different loading densities revealed an optimum selector density of about 310μmol/g chiral stationary phase with respect to resolution and selectivity. A decrease of performance was observed for higher loading, indicating mutual spatial influence of selector units leading to sterical hindrance. In addition, we observed that the effect of free azide groups on retention is negligible and the overall chromatographic behavior is comparable to other Cinchona derived chiral stationary phases.
Keywords: alkyny; Copper-catalysis; oxid křemičitý; Cycloaddition Reaction; Ion Exchange; iontová výměna; Stereoisomerism; Chiral anion exchange chromatography; Carbamates; chinidin; Click chemistry; cykloadiční reakce; azidy; Enantiomer separation; karbamáty; stereoizomerie; Azides; Quinine; Quinidine; Silicon Dioxide; Cinchona alkaloids; chromatografie; Alkynes; Chromatography; chinin; aminokyseliny; Click Chemistry; Liquid chromatography; Amino Acids; click chemie